Didactic Values in the Gending Text of the Baris Dadap Dance in Adat Batur Village, Bali - Pratama, Pande Putu Yogi Arista; Jazuli, Muhammad; Adnyana, I Wayan; Cahyono, Agus (Universitas Negeri Semarang, 2024)
The Baris Dadap dance is a sacred dance performed by four to six male dancers, typically staged during the Dewa Yadnya ceremony (a sincere and wholehearted offering to the Almighty God). The Baris Dadap dance has distinctive characteristics that set it apart from other types of Baris dances, particularly in its performance structure, which combines movements and gending (traditional Balinese song), referred to in Balinese as wirama. This study aims to (1) describe the performance form of the Baris Dadap dance and (2) analyze the didactic implications of the gending text in the Baris Dadap dance on the formation of knowledge within the Batur traditional village community in Bali. This research employs a qualitative method with data sources including the Baris Dadap dance performance, dancers, musicians, community elders, cultural figures, and journals related to previous research findings. Structural functional theory and Balinese dance theory are used to analyze all data collected through observation, interviews, and documentation. The results of the study indicate that (1) the performance form of the Baris Dadap dance is built on three main frameworks—dance movements, gending texts sung by the dancers, and accompanying music—with the structure of the performance divided into three parts: the first part called pepeson, the second part called pengadeng, and the third part called pekaad; (2) the didactic values in the gending text of the Baris Dadap dance have implications for the formation of a knowledge system in the aspects of tattwa (philosophy), susila (morality), and upacara (rituals). The new findings of this study reveal that the values embedded in traditional dances and their meanings can serve as a conscious means of imparting human knowledge to achieve physical and spiritual harmony.